Carefully prove that:

If $A,B,C$ are non-empty sets then $A \subseteq (B \cup C) \iff A \setminus C \subseteq B$.

So i need to prove

$A\subseteq(B\cup C) \implies (A\setminus C)\subseteq B$

and then

$(A\setminus C)\subseteq B \implies A\subseteq(B\cup C)$

So $x\in A$..

Can you provide the step by step proof please. Thank you in advance

  • $\begingroup$ There are usually no "step-by-step" answers in this site. Askers are expected to do some self effort on their own and complete to a whole answer. $\endgroup$ – DonAntonio Aug 30 '13 at 7:56
  • $\begingroup$ The statement is true even if one or more of the sets, $A,\,B$ and $C$ are empty. $\endgroup$ – Alraxite Aug 31 '13 at 0:50

Suppose $A\subseteq B\cup C$. Let $x\in A\setminus C$. Then $x\in A$ and from $A\subseteq B\cup C$, we conclude $x\in B\cup C$. Now use the fact that $x\not\in C$.

To prove the reverse implication, suppose $A\setminus C\subseteq B$ and let $x\in A$. Now consider two cases: $x\in C$ and $x\not\in C$.


For each side of the equivalence, expand the definitions and simplify. Finally compare the results.

For the left hand side, \begin{align} & A \subseteq B \cup C \\ \equiv & \;\;\;\;\;\text{"definition of $\;\subseteq\;$"} \\ & \langle \forall x :: x \in A \;\Rightarrow\; x \in B \cup C \rangle \\ \equiv & \;\;\;\;\;\text{"definition of $\;\cup\;$"} \\ & \langle \forall x :: x \in A \;\Rightarrow\; x \in B \lor x \in C \rangle \\ \equiv & \;\;\;\;\;\text{"rewrite $\;\Rightarrow\;$"} \\ & \langle \forall x :: x \not\in A \lor x \in B \lor x \in C \rangle \\ \end{align}

Do the same for the other side, compare, and conclude.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.